Subject-Orientation as a Means for Business Information System Design – A Theoretical Analysis and Summary - Elstermann, Matthes; Ovtcharova, Jivka (Business Information Systems, 2019)
(Business) Information systems become more and more complex due to an increase in the volume of data, but also due to more and more interconnected elements that all need to be orchestrated to perform as a uniform system. Correctly understanding and describing (business) processes, is one of the cornerstone foundations in the creation of almost all information systems. While the systems themselves have become more complex, and the means to program them have evolved over the last decades, the means to analyze and communicate about the processes they execute have stagnated on a simplistic level from the 1960s. Over the last 15 years, there has been work done in the development of concepts and tools on the topic of subject-orientation and subject-oriented (business) process modeling and management (S-BPM) that is different from earlier, classical process description approaches. This paper analyzes and argues about the shortcomings and discrepancies of those classical approaches and argues how subject-orientation may be an improvement when employed as a means in the design and development of information systems.